2010
DOI: 10.1111/j.1467-839x.2010.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐national examination of the perpetrator–victim account estimation bias as a function of different types of accounts

Abstract: In two cross-national studies, we investigated the existence of a perpetrator-victim account estimation bias and how this bias can be reduced or eliminated when estimating the perpetrator's use of a mixed account; that is, an account in which the perpetrator not only apologizes but also explains mitigating and justifiable circumstances. Japanese and American participants took either the perspective of the perpetrator or the victim and estimated the likelihood of the perpetrator's use of each account. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…In line with previous studies (Baumeister et al, 1990;Baumeister & Leary, 1995;Mikula et al, 1998;Takaku et al, 2010), we expected European Americans to exhibit self-serving biases in the construction of interpersonal transgression memories. We also expected Asians to exhibit such biases for the enhancement of positive self-views in interpersonal contexts, as well as to show relationship-serving biases to promote interpersonal affiliation and belongingness.…”
Section: Case Study 1: Interpersonal Transgression Memory and Self-acsupporting
confidence: 78%
See 2 more Smart Citations
“…In line with previous studies (Baumeister et al, 1990;Baumeister & Leary, 1995;Mikula et al, 1998;Takaku et al, 2010), we expected European Americans to exhibit self-serving biases in the construction of interpersonal transgression memories. We also expected Asians to exhibit such biases for the enhancement of positive self-views in interpersonal contexts, as well as to show relationship-serving biases to promote interpersonal affiliation and belongingness.…”
Section: Case Study 1: Interpersonal Transgression Memory and Self-acsupporting
confidence: 78%
“…People’s interpretation and memory for social interactions, particularly interpersonal transgressions, can greatly influence their relationship satisfaction (e.g., Karney & Coombs, 2000), evaluations of themselves and others (e.g., Takaku, Green, & Ohbuchi, 2010), and subjective well-being (Kitayama, Markus, & Masaru, 2000). Among the many factors that influence memory for interpersonal transgressions, self-serving motivation has been shown to play a particularly important role (e.g., Baumeister, Stillwell, & Wotman, 1990).…”
Section: Case Study 1: Interpersonal Transgression Memory and Self-acmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent excuses, for example, may lose any effectiveness (Schlenker, Pontari, & Christopher, ). Furthermore, prior research on social accounts has found important differences across cultures (Takaku, ; Takaku, Green, & Ohbuchi, ; Takaku, Weiner, & Ohbuchi, ). Future work should examine the extent to which our findings apply in other cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Scott and Lyman (1968) define an account as “a linguistic device employed whenever an action is subjected to valuative inquiry” (p. 46); other scholars conceptualize “verbal account” (Elsbach, 1994, p. 58) or “social account” (Bies, 1987, p. 289). Most conceptualizations include any kind of verbal explanation (e.g., Giacalone & Pollard, 1990; Takaku, Green, & Ohbuchi, 2010), which refers to deviant behavior or negative events (e.g., Bennett, 1980; Scott & Lyman, 1968; Sonenshein, Herzenstein, & Dholakia, 2011). Moreover, accounts can focus on the past or the future; Goffman (1972) labeled the latter “requests.” To sum up, we define accounts as verbal explanations of social actors toward another social actor about past and/or future events.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%